2010
DOI: 10.1097/hpc.0b013e3181ec36d8
|View full text |Cite
|
Sign up to set email alerts
|

Chest Pain in the Emergency Room

Abstract: The HEART score helps in making accurate diagnostic and therapeutic decisions without the use of radiation or invasive procedures. The HEART score is an easy, quick, and reliable predictor of outcome in chest pain patients and can be used for triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(126 citation statements)
references
References 17 publications
9
113
2
2
Order By: Relevance
“…Hence, the HEART score was not developed using logistic regression modeling upon a real‐life database. Although male sex was reported to be a statistically significant predictor of MACE occurrence in previous HEART score validation studies, the HEART algorithm maintained similar discriminatory accuracy among men and women 14, 24, 25. In the prospective multicenter HEART score validation study, for example, Backus et al25 reported 6‐week MACE rates of 11.4% (116 of 1016) in women and 21.2% (291 of 1372) in men, with AUCs of 0.82 and 0.83, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Hence, the HEART score was not developed using logistic regression modeling upon a real‐life database. Although male sex was reported to be a statistically significant predictor of MACE occurrence in previous HEART score validation studies, the HEART algorithm maintained similar discriminatory accuracy among men and women 14, 24, 25. In the prospective multicenter HEART score validation study, for example, Backus et al25 reported 6‐week MACE rates of 11.4% (116 of 1016) in women and 21.2% (291 of 1372) in men, with AUCs of 0.82 and 0.83, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Myocardial necrosis can often be confirmed or excluded within 1 to 3 hours,11, 12 but the interpretation of troponin levels depends on clinical context and repeated measurements. The HEART score13, 14 is a simple and effective clinical prediction rule incorporating both clinical context— H istory, E lectrocardiograph, A ge and R isk factors—and admission T roponin levels. Using solely information collected at time of presentation, the HEART score is able to accurately estimate a patient's short‐term cardiac risk, taking into account not only the risk of myocardial infarction during the index visit, but also major adverse cardiac events (MACE) that occur in the first 6 weeks thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…ADPs required troponin measurement on arrival and then at 1, 2, or 3 hours to determine eligibility for early discharge. ADPs that were considered were the 2-Hour Accelerated Diagnostic Protocol to Assess Patients With Chest Pain Symptoms Using Contemporary Troponins as the Only Biomarker (ADAPT) 10,14 ; Emergency Department Assessment of Chest Pain Score (EDACS) 15,17,18 ; History, ECG, Age, Risk Factors, and Troponin (HEART) 11,19 ; the High Sensitivity Cardiac Troponin T Assay for Rapid Rule-Out of AMI (TRAPID-AMI) 20,21 ; and the new Vancouver Chest Pain Rule. 13 Before implementation, there were meetings involving the first author and representatives from each stakeholder group (including but not limited to the ED, cardiology, general medicine physicians and nurses, hospital management, diagnostic laboratory directors, cardiac technicians, and hospital data analysts).…”
Section: Intervention Phasementioning
confidence: 99%
“…8,[10][11][12][13] Randomized implementation trials of clinical pathways incorporating ADPs at Christchurch Hospital (Christchurch, NZ) demonstrated that early safe discharge rates could be improved (from 11.0% to 32.3%). 14,15 Immediate and successful implementation of clinical pathways incorporating an ADP at Christchurch Hospital prompted the New Zealand Ministry of Health to mandate that all hospitals implement similar clinical pathways for possible ACS.…”
mentioning
confidence: 99%
“…The HEART score (History, ECG, Age, Risk Factors, Troponin), for example, uses elements of the patient's history, ECG findings, age, risk factors for coronary artery disease and initial coronary artery disease to identify a group of patients that could be immediately discharged. 12 AMI could potentially also be 'ruled out' in patients with hs-cTnT concentrations below the limit of detection of the assay and no ECG ischaemia. [13][14][15][16] Other tools, such as the Emergency Department Assessment of Chest Pain Score (ED-ACS) or bespoke algorithms to rule out AMI with hs-cTnT testing alone, could be used to discharge more patients following serial troponin testing after 1 to 2 hours.…”
Section: Future Directionsmentioning
confidence: 99%